Impact of ocean observations on decadal climate prediction with the ECMWF coupled forecast system - Doblas- Reyes, Francisco Javier (Física de la Tierra, 2010)
Decadal forecasting is a new field that aims at providing useful interannual climate information making the most of the best available observations. Initialising the ocean-atmosphere coupled models employed in dynamical decadal forecasting is a requirement. Two commonly used strategies for initializing seasonal forecasts have been employed in a set of ten-year ensemble reforecasts carried out with the ECMWF coupled model. The forecast system is similar to the one used for seasonal forecasting, except for a refined treatment of greenhouse gas concentrations and sulphate aerosols. The interannual predictions formulated from the set of simulations show that the system has skill in predicting global and regional mean temperature up to several years in the future, especially over the tropics, where the influence of the skilfully predicted ocean heat content directly influences the atmosphere aloft. The interpretation of the estimates of the beneficial impact of the ocean observations found over the tropics and for certain ocean variables suffers from the shortness of the sample (typical of the experiments devised for the fifth Coupled Model Intercomparison Project), the lack of reliable observations and the sizeable model systematic error.